Impact parameter sensitive study of inner-shell atomic processes in Xe54+, Xe52+ → Xe collisions. Issue 14 (January 2020) - Gumberidze, A; Kozhuharov, C; Zhang, R T; Trotsenko, S; Kozhedub, Y S; Du, R D; Bois, H; Beyer, F.; Blumenhagen, K-H; Brandau, C; Bräuning-Demian, A; Chen, W; et al.
Synopsis: In this work, we present a pilot experiment in the experimental storage ring (ESR) at GSI devoted to impact parameter sensitive studies of inner shell atomic processes for bare and He-like xenon ions (Xe 54+, Xe 52+ ) colliding with neutral xenon gas atoms. The projectile and target x-rays have been measured at different observation angles for all impact parameters as well as for the impact parameter range of ∼35 - 70 fm.